2021
DOI: 10.3389/fonc.2021.683042
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Assessing the Impact of Palliative Radiotherapy on Quality of Life and Symptom Burden in Head and Neck Cancer Patients: A Systematic Review

Abstract: Incurable head and neck cancer has a poor prognosis and impairs a patient’s health-related quality of life. Palliative radiotherapy may improve or stabilize health-related quality of life and symptoms, best measured by patient-reported outcomes. There is no systematic analysis if palliative radiotherapy for head and neck cancer improves or stabilizes health-related quality of life or symptoms as validly measured by patient-reported outcomes. Therefore, the primary objective of this systematic review (PROSPERO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…In our study, only 8 patients (53%) turned up for follow up visits. There are chances of missing data which gives us wrong interpretation [11]. Murthy et al reported significant attrition rate in their study [14].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In our study, only 8 patients (53%) turned up for follow up visits. There are chances of missing data which gives us wrong interpretation [11]. Murthy et al reported significant attrition rate in their study [14].…”
Section: Discussionmentioning
confidence: 95%
“…Radiation therapy in curative doses leads to significant toxicity and further negatively impacts the quality of life of incurable patients. Incurable head and neck cancer patients have limited survival [11]. Prognostifying patients in an incurable setting is a difficult task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most published series have shown comparable outcomes in respect to survival , symptomatic improvement and quality of life irrespective of dose and fractionation used. 9,10,12,14,16,17 Radiation oncologist individualises treatment decision according to the assessment of the patient's symptoms, disease burden, comorbidities, performance status, weight loss, and anemia etc., also taking into the personal consideration of the patient. Therefore the fractionation scheme used becomes a surrogate for such factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experience has shown that stereotactic RT, in different clinical scenarios, could lead to improved quality survival compared to conventional RT, also in emerging centers [16][17][18][19]. Stereotactic RT, with the reduction of treatment course, resulted in higher compliance and adherence to treatment schedule even for old patients and in palliative setting [20][21][22]. An alternative approach for the treatment of BC including neoadjuvant RT has been investigated; evidence has shown that the combination of neoadjuvant chemotherapy and RT can result in a potential benefit in terms of tumor control and tolerance [23,24].…”
Section: Introductionmentioning
confidence: 99%